POLA-POLA KOMUNIKASI NELAYAN DALAM MEWUJUDKAN KETAHANAN PANGAN RUMAHTANGGA NELAYAN DI KOTA BENGKULU (KASUS PADA NELAYAN KAPAL KECIL) - Mulyasari, Gita; Arianti, Nyayu Neti (Jurnal AGRISEP, 2015)
Some earlier results showed that there were 43% of the families belonging to the famine did not get help from the local community when food shortages. By looking at these conditions, this study was designed to examine how fishermen communication patterns in their interaction with the social environment in order to achieve food security in the household. Respondents were drawn from a group of fishermen called the Kelompok Usaha Bersama (KUB) in Pulau Baai. From an interview with the head of a group of fishermen, the number of fishermen using small boats is 24 households. This research results showed there were two fishermen communication patterns in discussing household food security issues, namely, the interpersonal communication and group communication. Interpersonal communication patterns involving informations from other fishermen. Messages are widely discussed is everything associated with their fishing fishing effort. Among the existing group communication, group discussion fishermen have an impact on the fishing action in carrying out their fishing effort. Advances in fishery business can increase revenue and will also have an impact on the family's food security.